Challenges, strengths, and relevance of integrating classroom-based assessment in technical and vocational education training - Siti Raudhah M. Yusop; Mohamad Sattar Rasul; Ruhizan Mohamad Yasin (International Journal of Evaluation and Research in Education (IJERE), 2024)
Technical and vocational education training (TVET) assessment is critical to determine the intended learning outcomes for students. However, the TVET assessment presents several essential obstacles, such as assessing occupational skills disconnected from lesson-learning results. Assessment methods are another contentious topic among academics and other professionals because teachers’ different methods of evaluating students’ work are incompatible with assessment objectives and are a significant issue in TVET assessment. Consequently, this research investigates the challenges and strengths of classroom assessment practices and the relevance of implementing vocational skills. This research uses a quantitative survey methodology to assess the degree of participants agree using descriptive analysis. The study’s findings indicate several challenges associated with administering classroom-based assessment (CA) within the context of TVET. CA is an excellent venue for assessing the students’ acquired knowledge and abilities in education. The TVET assessment must include, in addition to technical skills, generic skills related to Industry 4.0 and career adaptability skills as a student’s learning outcomes. These skills serve as the basis for the development of skills and competencies. Cognitive, psychomotor, and interpersonal qualities are vital in the TVET assessment as a student learning outcome.